Praktik Politik Uang Pada Pemilihan Kepala Daerah DKI Jakarta Tahun 2024: Studi Komparasi Kota Administrasi Jakarta Pusat dan Jakarta Selatan - Mohammad Reyhan Ardhito Nugroho; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2026)
This study aims to analyse the dynamics of money politics practices and evaluate the effectiveness of prevention efforts during the 2024 Jakarta Regional Head Election (Pilkada) through a comparative study between the Administrative Cities of Central Jakarta and South Jakarta. Employing a qualitative method that integrates the Patronage-Clientelism theory, George C. Edwards III's Policy Implementation model, and a cultural approach, this research reveals that the modus operandi of money politics is highly adaptive to the local socio-cultural ecosystem. In the communal setting of Central Jakarta, the practice operates conventionally through "dawn raids" (serangan fajar), taking refuge behind the culture of ewuh pakewuh (feeling of discomfort to refuse) and strong neighbourhood ties, whereas in the individualistic, middle-class-dominated South Jakarta, the practice transforms into club goods or disguised functional programs such as subsidized markets (pasar murah). Regarding the supervisory aspect, policy implementation by the General Election Supervisory Agency (Bawaslu) has proven ineffective due to resource limitations and technical application constraints, structural gridlocks within the Integrated Law Enforcement Center (Sentra Gakkumdu), the vulnerability of ad-hoc supervisors' integrity, and communication distortions caused by the strong cultural rationalization of the community, which normalizes money politics as a "blessing" (rezeki) or an acceptable tradition. In conclusion, money politics persists because broker networks adeptly exploit supervisory loopholes, thereby reaffirming the failure of the electoral justice system when rigid procedural law enforcement severely collides with permissive cultural realities at the grassroots level.